The Properties improvement of rice starch films by cooperated with cellulose and crystalline cellulose from palm pressed fiber - Phattaraporn Thongsane (Prince of Songkla University, 2013)
Thesis (M.Sc., Packaging Technology)--Prince of Songkla University, 2009